Growth Performance and Haematological Indices of Broiler Chickens Fed on Rice Husk Supplemented with Oyster Mushroom (Pleurotus ostreatus) and Brozyme Enzyme - Dairo , F.A.S.; Ogunlade, S.W. (International Journal of Poultry Science, 2022)
Objective: The present study aimed to investigate the effects of native rice husk on the growth performance and haematology of Broiler Chickens. Materials and Methods: A total of 210 day old broiler chicks of Arbor Acre breeds were fed starter and finisher diets containing (I) Pleurotus ostreatus fungus fermented rice husk (PFFRH) and (ii) exogenous brozyme enzyme supplemented rice husk (ESRH). Different levels of the test feeds (10, 20 and 30%) were included in the broiler diets to replace maize at the two phases. The birds were distributed in a completely randomized design to make a 2×3 factorial arrangement that gave 7 treatments and 3 replicates with 10 birds in each replicate. Results: The results showed that birds fed on the control diet and 10% PFFRH inclusion in the diet, had the highest (p